Role of Charismatic Leadership and Technology Self-Efficacy in HRIS Use Behavior: A Conceptual Study - Perera, A H U; Jayawardana, A K L (Journal of Management and Research, 2022)
The current study claims that the Human Resource Information System (HRIS) Use Behavior, plays a salient role in utilizing the information technology as intended. Thus, organizations investing in information technology are in dire requirement of developing and implementing the effective interventions. The purpose of this is to optimize information technology adoption and its maximum usage among the HRIS users. The existing knowledge base in HRIS Use Behavior hardly addresses the relationship of Charismatic Leadership and Technology Self-Efficacy in the Unified Theory of Acceptance and Use of Technology (UTAUT). The current study has developed an ‘integrative conceptual model’ contributing a theoretical extension of the UTAUT model, which fills he identified theoretical gaps, grounded on UTAUT, Charismatic Leadership theory, and the Social Cognitive Theory. The salient feature of this study is that it conceptualizes and introduces two constructs: 1) Technology Self-Efficacy and 2) Charismatic Leadership, in extending a validated information system Use Behavior or ‘explanatory model’ as a theoretical contribution. This concept paper argues that the Charismatic Leadership and Technology Self-Efficacy have a positive relationship among the UTAUT model’s HRIS Use Behavior-related variables. However, it can be integrated towards arriving at a ‘coherent conceptual model’ to be researched and validated. This particular study has developed a ‘coherent conceptual framework’ in studying the phenomenon of HRIS Use Behavior. Furthermore, it studies the role of Charismatic Leadership and Technology Self-Efficacy in affecting the psychological aspect of the end users of a Human Resource Information System (HRIS)